Congenital pneumonia due to Mycoplasma pneumoniae. Issue 2 (March 1995) - Ursi, D.; Ursi, J. P.; Ieven, M.; Docx, M.; Van Reempts, P.; Pattyn, S. R.
Abstract : A case of probable vertical transmission of Mycoplasma pneumoniae is presented. The presence of M pneumoniae was demonstrated by the polymerase chain reaction (PCR) in the nasopharyngeal aspirate of a newborn who developed pneumonia shortly after birth. This result was confirmed by performing a second PCR, amplifying another part of the genome of M pneumoniae. It is concluded that M pneumoniae can be added to the long list of pathogens known to cause congenital pneumonia.